Decentralization and democratic governance - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Decentralization is often part of a number of related policy reforms, in which central government agencies transfer rights and responsibilities to more localized institutions. Although there are a number of different types of reforms that are sometimes referred to as “decentralization,” most call for some kind of greater organized involvement of local people.